Effect of Caffeine-Containing Beverages on Physicochemical and Release Properties of Halofantrine (Global Journal of Medical Research, 2014)
Halofantrine (Hf) is a poorly water-soluble drug for treating malaria in endemic areas like tropical Africa, where caffeine-containing products are habitually consumed. Previous reports showed that caffeine increased the aqueous solubility of Hf at room temperature over 3 days. The aim of this study was to determine the effect of caffeine and caffeine-containing beverages on dissolution and solubility of Hf and to investigate any possible interactions. The aqueous solubility and dissolution of Hf alone and in the presence of caffeine was investigated at pH 1.3, 5.9 and 7.4 using standard methods. The solubility of Hf in the presence of aqueous extracts of cocoa, coffee, black tea and green tea at pH 5.9 was also investigated. In 1 hour, caffeine markedly increased the aqueous solubility of Hf at pH 1.3, 5.9 and 7.4. Caffeine and caffeine-containing beverages markedly increased the aqueous solubility of Hf by between 100-to more than 1600-fold, with a 1672-fold increase by caffeine (from 76.6 ±7.8 ng/mL to128.2 ± 4.5 mg/mL) at pH 5.9. The dissolution of Hf tablets at pH 1.3, 5.9 and 7.4 showed the respective amounts released as 3.57 ± 0.09, 0.95 ± 0.19 and 0.260 ± 0.043 mg, but introduction of caffeine increased these values to 9.51 ± 0.23, 3.70 ± 0.12 and 0.52 ± 0.10 mg respectively, representing 3-fold, 4-fold and 2-fold respectively.
Keywords: caffeine; halofantrine; physicochemical interaction